Career Guidance for Students of Grade XI IPA SMAN 8 Tanjung Jabung Timur - Hidayat, M.; Dani, Rahma; Sanusi, Anwar; Hudaya, Padhil; Saputra, Ade Bayu; Al-Rawafi, Abdulkhaleq (Jurnal Al Maesarah, 2024)
The school is required to assist students in determining choices according to their interests and talents and to assist them make plans to realize the decisions that have been taken. The activities carried out are career guidance that provides students. Guidance participants are class XI students at SMAN 8 Tanjung Jabung Timur. The activity begins with the preparation stage, followed by a report on the results of community service activities. The time needed is six months, starting from April to September 2023. The methods used in this guidance activity are lectures, discussion methods, and question-and-answer methods. The material provided is in the form of knowledge about work and continuing studies at university. The desired output of this activity is to increase students' understanding of SMA Negeri 8 Tanjung Jabung Timur in the field of work and continue their studies at university. The data were questionnaires distributed to 21 students at the beginning and end of the activity, an average increase in student understanding was obtained from 39.86 to 42.71. If calculated, the N Gain is 0.31, included in the moderate category. Thus, this activity has succeeded in increasing students' awareness of career choices in the future